Enteric duplication cyst—a peculiar aetiology of anaemia in a two-year- old boy: a case report - Fanzer Khan; Eeman, Nabiha; Ahsan Ali Mirza; Atta ul Rehmen Saadi (Journal of the Pakistan Medical Association, 2026)
Enteric duplication cysts are rare congenital malformations of gastrointestinal tract that are characterised by the presence of epithelial lining of intestinal mucosa, a layer of smooth muscle and a common wall with the GI tract that may or may not show communication with the gut lumen. On the basis of structural classification, enteric duplication cysts can be either cystic or tubular. This case report is about a two-year-old boy who presented to the Outpatient Department of Paediatrics at the PAEC General Hospital, Islamabad, with complaints of black tarry stools and lethargy since two months and cough since one month. He had a history of multiple blood transfusions. After detailed examination and investigations, diagnosis of thoracic enteric duplication cyst was proposed. Thoracic cystectomy was done. Diverging from its usual respiratory or dysphagic manifestations, this thoracic enteric duplication cyst (extending above into the neck and below into the parahepatic space) presented as a diagnostic enigma through severe anaemia and gastrointestinal bleeding, highlighting its extraordinary rarity. Keywords: Anaemia, (D000740), Cyst (D003560), Congenital abnormality (D000013).